ENHANCING THE DIGITAL CAPACITY OF LOCAL CULINARY MSMES THROUGH CREATIVE CONTENT TRAINING ON INSTAGRAM AND TIKTOK - Muhamad Al Faruq Abdullah; Magito; Wenny Desty Febrian (Universitas Sahid, 2025)
This community service initiative aimed to strengthen the digital marketing capabilities of local culinary MSMEs in Jatimekar, Bekasi, by providing hands-on training on the use of Instagram and TikTok for promotional purposes. Conducted on June 15, 2025, the program involved 25 participants from small-scale food and beverage enterprises. The training covered digital promotion strategies, content creation using tools like Canva and CapCut, and techniques for enhancing brand awareness through storytelling and visual media. Implemented through interactive sessions and direct mentoring, the program resulted in increased participant understanding of digital marketing and improved confidence in creating promotional content. Post-training evaluations showed that over 80% of participants successfully produced and shared content on social media platforms. The initiative demonstrated the effectiveness of structured and participatory digital literacy programs in supporting sustainable business growth and expanding market reach for MSMEs in the digital economy.